Persistence of unsafe practice in everyday work: an exploration of organizational and psychological factors constraining safety in the operating room. Issue 3 (2nd June 2006) - Espin, S; Lingard, L; Baker, G R; Regehr, G
Abstract : This paper explores the factors that influence the persistence of unsafe practice in an interprofessional team setting in health care, towards the development of a descriptive theoretical model for analyzing problematic practice routines. Using data collected during a mixed method interview study of 28 members of an operating room team, participants' approaches to unsafe practice were analyzed using the following three theoretical models from organizational and cognitive psychology: Reason's theory of "vulnerable system syndrome", Tucker and Edmondson's concept of first and second order problem solving, and Amalberti's model of practice migration. These three theoretical approaches provide a critical insight into key trends in the interview data, including team members' definition of error as the breaching of standards of practice, nurses' sense of scope of practice as a constraint on their reporting behaviours, and participants' reports of the forces influencing tacit agreements to work around safety regulations. However, the relational factors underlying unsafe practice routines are poorly accounted for in these theoretical approaches. Incorporating an additional theoretical construct such as "relational coordination" to account for the emotional human features of team practice would provide a more comprehensive theoretical approach for use in exploring unsafe practice routines and the forces that sustain them in healthcare team settings.